Easily English Sentences Understanding by the Syntax Method in Class XI A of SMA Muhammadiyah 3 Jember - Ageng Soeharno; Mohammad Thamrin; Edhi Siswanto; Achmad Syahfrudin Zulkarnnaeni (Journal Of Humanities Community Empowerment, 2025)
In this training, students are guided to understand sentences using the syntax method. Syntax is a framework of rules that describes how all well-structured sentences in a language can be generated from basic components (morphemes, words, and parts of speech). The depiction of the sentence construction framework here uses the Backus-Naur Form technique. Backus–Naur Form (BNF) is a formal metalanguage used to structure the syntax and rules of programming languages. Created in the late 1950s by American computer scientist John Backus, BNF serves as a regular notation that helps developers ensure that the code they write follows a specific set of rules, similar to grammar guidelines for everyday languages. This notation utilizes various symbols, such as square brackets, to indicate defined categories and terms, thus clearly describing the structure of the language. This training was attended by 17 male and female students of SMA Muhammadiyah 3 Jember, involving 4 resource persons. The training took place solemnly, emphasizing a sense of camaraderie to foster positive communication among participants. Evaluation results showed satisfactory results, with students improving their comprehension, spelling, and translation skills.